Does software design complexity have effects on defects - Awang Abu Bakar, Normi Sham (INSI Publications, 2013)
Empirical analysis is an important area in software engineering. One of the ways to ensure the quality of any software is to measure the software using statistical analysis of various metrics from empirical data. The emergence of various open source software repositories has contributed tremendously to the advancement in the empirical software engineering research. This paper presents an empirical analysis using a set of metrics such as Structural, Data, Procedure and System Complexity, as well as Class Size on open source data. The results show that only CBO is significant in predicting defects.